A DEVELOPMENT OF USER EXPERIENCE (UX) GUIDELINE FOR CHILDREN EDUCATIONAL MOBILE APPLICATION. - KAUR, KIRANJEET (2021)
Mobile learning has proven to be an essential tool while creating innovative and interactive process as it is easily portable as well as accessible anywhere. Even though, the use of mobile learning is popular among children these days yet, only limited studies have portrayed the effectiveness of utilizing it well which caused the users to experience similar activities and design in the mobile application. With this the problem statement could be identified that designers and developers are not given proper guidance when developing mobile application for children mainly to learn instead they are given instructions only to improve the atheistic and instead of understanding how children could get attracted with the application designers are producing games.